2012
DOI: 10.1093/jac/dks142
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of linezolid versus a pharmacodynamically optimized vancomycin therapy in an experimental pneumonia model caused by methicillin-resistant Staphylococcus aureus

Abstract: These results support that a vancomycin AUC₀₋₂₄/MIC ratio >400 is necessary to obtain a high bacterial lung reduction in MRSA pneumonia, comparable to that achieved with linezolid and better than that with the low dose of vancomycin tested. Linezolid was more efficacious than the pharmacodynamically optimized vancomycin dose in the pneumonia caused by the most virulent strain (MR33).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Using an experimental murine model of MRSA pneumonia, our group found that an optimized dose of vancomycin (AUC/ MIC ratio Ն 400) was more efficacious than lower doses of vancomycin in the clearance of bacteria from lungs and blood, even though it could not demonstrate a higher survival rate (20). In clinical studies, an AUC/MIC ratio around 400 is related to the best survival rate or to clinical success in patients with S. aureus bacteremia, although other thresholds have been observed (10,17,18,21).…”
Section: Vancomycin Pharmacodynamics and Its Implications For Drug Momentioning
confidence: 99%
“…Using an experimental murine model of MRSA pneumonia, our group found that an optimized dose of vancomycin (AUC/ MIC ratio Ն 400) was more efficacious than lower doses of vancomycin in the clearance of bacteria from lungs and blood, even though it could not demonstrate a higher survival rate (20). In clinical studies, an AUC/MIC ratio around 400 is related to the best survival rate or to clinical success in patients with S. aureus bacteremia, although other thresholds have been observed (10,17,18,21).…”
Section: Vancomycin Pharmacodynamics and Its Implications For Drug Momentioning
confidence: 99%
“…Treatment of these infections is complicated by the fact that ϳ50% of S. aureus isolates from patients with pneumonia are methicillin-resistant S. aureus (MRSA), thereby reducing safe and effective treatment options (1). While vancomycin (VAN) is the primary therapy for MRSA pneumonia, the mortality rate in pneumonia patients treated with vancomycin remains high, and the emergence of intermediate resistance to glycopeptides potentially limits the usefulness of this class of antibiotics (3)(4)(5). Linezolid (LZD) is currently the only other drug with anti-MRSA activity that is approved for the treatment of nosocomial pneumonia in the United States and Europe (4,6).…”
mentioning
confidence: 99%
“…Some studies using pneumonia animal models have demonstrated that linezolid was more effective than vancomycin toward this type of infection due to its better penetration into the lung. Therefore, it was suggested that linezolid might be chosen for MRSA pneumonia cases with increased vancomycin minimum inhibitory concentration ( Docobo-Pérez et al 2012 , Martinez-Olondris et al 2012 , Rodvold & McConeghy 2014 ). Daptomycin, which is a cyclic lipopeptide, was launched in the USA in 2003 for the treatment of skin/soft tissue infections (SSTI) caused by MRSA and other microorganisms and good results have been reported for this drug for the treatment of BSI and endocarditis caused by these microorganisms ( Rodvold & McConeghy 2014 ).…”
mentioning
confidence: 99%